High-dose spinal cord stimulation for patients with failed back surgery syndrome: a multicenter effectiveness and prediction study. Issue 2 (February 2021) - Goudman, Lisa; De Smedt, Ann; Eldabe, Sam; Rigoard, Philippe; Linderoth, Bengt; De Jaeger, Mats; Moens, Maarten
Abstract : Abstract: The use of high-dose spinal cord stimulation (HD-SCS) has increased drastically during the past few years, with positive results. However, there remains a deficit of real-world data of the effectiveness of HD-SCS. Therefore, the primary aim was to evaluate the effectiveness of HD-SCS in patients with failed back surgery syndrome (FBSS). The second aim was to develop a prediction model for a holistic responder. One hundred ninety-four patients were recruited to a multicenter real-world registry. Self-reporting outcome variables were evaluated at baseline (before SCS) and at 1, 3, and 12 months of HD-SCS implant. Outcome measures were the mean pain intensity over time, sleep quality, disability, health-related quality of life, and medication use. Besides the effectiveness, logistic regression and decision tree analysis were performed to define a holistic responder (pain intensity reduction, medication reduction, Oswestry disability index reduction, and EQ5D improvement) after 12 months of HD-SCS. Of 185 FBSS patients who underwent a baseline visit, 75.13% had a successful HD trial. At 12 months, 92 patients were still receiving HD-SCS. Both low back and leg pain significantly decreased at 12 months. All outcome measures revealed a significant time-dependent effect from baseline to 12 months. Holistic responders could be predicted with a sensitivity and specificity of 90%. Clinically significant and sustained pain relief over a period of 12 months was achieved with HD-SCS in patients with FBSS. In addition, HD-SCS also achieved an improvement in sleep quality, functionality, and a decrease in pain medication. Abstract : High dose spinal cord stimulation is a valid option for failed back surgery syndrome to obtain back and leg pain relief after 1 year. High-dose spinal cord stimulation also improves sleep quality, functionality, and quality of life, and reduces pain medication intake.